Physical education (PE) for improving skills of special needs students - I Gede Suwiwa; I Ketut Budaya Astra; I Gede Doddy Tisna M.S; I Made Satyawan; I Made Gede Arta Mahardika (Physical Education Departement of University PGRI Jombang, 2025)
Physical Education (PE) can improve special needs students’ skills, competencies, and accommodate social behaviours from several aspects, such as cognitive, motoric, and social aspects. Physical Education becomes an important and essential role in improving the special needs students’ quality of life. This study aims to provide a systematic and scientific reviews regarding to the improvement and positive impacts of Physical Education for special needs students. The findings of this study showed that: (1) The Importance of Physical Education for Special Needs Students and (2) The Improvement Skills of Special Needs Students through Physical Education. As the results, Physical Education gives a great and many opportunities to special needs students, which it caused by the improvement in the concentration and cognitive skills. On the other hands, it also gives various important things, such as stimulate the special needs students’ mindset, movements, and psychomotor.